Does Psychedelic Therapy Have a Transdiagnostic Action and Prophylactic Potential? - Kočárová, Rita; Horáček, Jiří; Carhart-Harris, Robin (Frontiers in Psychiatry, 2021)
Addressing global mental health is a major twenty-first century challenge. Current treatments have recognised limitations; in this context, new ones that are prophylactic and effective across diagnostic boundaries would represent a major advance. The view that there exists a core of transdiagnostic overlap between psychiatric disorders has re-emerged in recent years, and evidence that psychedelic therapy holds promise for a range of psychiatric disorders supports the position that it may be transdiagnostically effective. Here we propose that psychedelic therapy’s core, transdiagnostically relevant action, lies in its ability to increase neuronal and mental plasticity, thus enhancing the potential for change, which we consider to be a key to its therapeutic benefits. Moreover, we suggest that enhanced plasticity via psychedelics, combined with a psychotherapeutic approach, can aid healthy adaptability and resilience, protective factors for long-term well-being. We present candidate neurological , and psychological markers of this plasticity and link them with a predictive processing model of the action of psychedelics. We propose that a model of psychedelic induced plasticity combined with an adequate therapeutic context has prophylactic and transdiagnostic potential, implying that it could have a broad, positive impact on public health.